Design, synthesis and determination of biological activities of stilbene analogue attached to zinc (ii)-cyclen complex / Nafiza Mohd Ismail - Mohd Ismail, Nafiza (2005)
The significance of this research is to design, synthesis and determination of biological activities of resveratrol (stilbene) analogue attached to Zn2+-cyclen complex. Three established reactions had been used in order to accomplish the research. First, the 3,5- dimethoxybenzaldehyde was utilizes as a starting material of the Wittig reaction. Subsequently, protection of the 4-iodophenol using TBDMS-C1 to yield 4-iodo-tert- butyldimethylsilylphenylether. Product of the Wittig reaction and 4-iodo-/er/- butyldimethylsilylphenylether were then use to synthesize the stilbene analogue. The synthesized compounds were then, purified by chromatographic techniques and sent for 'H-NMR and UV characterization. The outcomes of this research did not make the grade, and the research was postponed due time constraint.